1982
DOI: 10.1021/jo00138a008
|View full text |Cite
|
Sign up to set email alerts
|

Cyclopentanone synthesis by intramolecular carbon-hydrogen insertion of diazo ketones. A diterpene-to-steroid skeleton conversion

Abstract: Intramolecular carbon-hydrogen insertion on cupric sulfate assisted decomposition of diazomethyl ketones derived from four l-methylcycloalkanecarboxylic acids and (hexahydrophenyl)acetic, homopivalic, and enanthic acids is shown to yield mostly cyclopentanones. The yields are appreciable in the conformationally favorable cases, and insertion in the solvent cyclohexane can be avoided by the use of Freon TF as the solvent The conversion of a pimaradienic diterpene into a 14-iso-16-androstanone derivative shows t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

1988
1988
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(33 citation statements)
references
References 1 publication
0
33
0
Order By: Relevance
“…Selective intramolecular C-H insertion provided β-ketoester 18 in excellent yield 33. Treatment of β-ketoester 18 with arylsilyl triflate 17 , available in 5 steps from sesamol,34 in the presence of cesium fluoride22a afforded ketoester (±)- 16 , thereby generating the polycyclic carbon framework of amurensinine in rapid fashion.…”
Section: Resultsmentioning
confidence: 99%
“…Selective intramolecular C-H insertion provided β-ketoester 18 in excellent yield 33. Treatment of β-ketoester 18 with arylsilyl triflate 17 , available in 5 steps from sesamol,34 in the presence of cesium fluoride22a afforded ketoester (±)- 16 , thereby generating the polycyclic carbon framework of amurensinine in rapid fashion.…”
Section: Resultsmentioning
confidence: 99%
“…Wenkert et al first applied this reactivity in the context of an intramolecular reaction. [156] In this case,C À Cb ond formation occurs at the allylic CÀHb ond of a-diazo ketone 371,w ith dirhodium acetate as ac atalyst, to give cyclopentanone 372.T abera nd Petty found that unactivated C(sp 3 )ÀHb onds also undergo the reaction, as exemplified by the formation of cyclopentanone 374 from a-diazo-b-keto ester 373 through the transfer of acarbene. [157] Themechanism of the C À Hinsertion step is believed to be concerted, but asynchronous,leaving apartial positive charge at the carbon atom of the CÀHbond.…”
Section: Carbene Transfermentioning
confidence: 99%
“…In this respect, CH insertions are more characteristic, and their occurrence provides strong evidence for carbenoid reactions. Rh"-Catalyzed diazo decompositions led often to substantial amounts of insertion products when appropriate precursors were used [31]. The intramolecular insertion of diazo ester 13b reportedly proceeded with [Rh,(OAc),] to the cyclic keto ester 14 in 95 YO yield [32].…”
Section: Rel To Styrene (3a)mentioning
confidence: 99%